2007
DOI: 10.1037/0278-6133.26.4.437
|View full text |Cite
|
Sign up to set email alerts
|

Self-affirmation reduces smokers' defensiveness to graphic on-pack cigarette warning labels.

Abstract: Self-affirmation can promote less defensive responding even to visual material about well-established health risks such as smoking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
247
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 200 publications
(265 citation statements)
references
References 44 publications
14
247
0
2
Order By: Relevance
“…For example, Reed and Aspinwall, (1998) found no evidence that self-affirmation was associated with participants reporting decreased caffeine consumption. Similarly, Harris et al (2007) reported no impact of selfaffirmation on self-reported reduction in number of cigarettes smoked at one-week follow-up. Indeed, there is a need for further research to explore the parameters that may influence when positive changes in cognitions arising as a result of self-affirmation are more or less likely to lead to changes in subsequent health behaviour.…”
Section: The Capacity Of Self-affirmation To Promote Positive Behaviomentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Reed and Aspinwall, (1998) found no evidence that self-affirmation was associated with participants reporting decreased caffeine consumption. Similarly, Harris et al (2007) reported no impact of selfaffirmation on self-reported reduction in number of cigarettes smoked at one-week follow-up. Indeed, there is a need for further research to explore the parameters that may influence when positive changes in cognitions arising as a result of self-affirmation are more or less likely to lead to changes in subsequent health behaviour.…”
Section: The Capacity Of Self-affirmation To Promote Positive Behaviomentioning
confidence: 99%
“…Thus, Harris et al (2007) reported that self-affirmed smokers rated graphic on-pack cigarette warning labels as more threatening and personally relevant, compared to individuals in the control condition. Moreover, self-affirmed smokers reported more negative thoughts and feelings, greater levels of perceived behavioural control, more positive intentions and higher self-efficacy in relation to reducing their smoking behaviour, compared to non-affirmed participants.…”
Section: The Capacity Of Self-affirmation To Promote Positive Changesmentioning
confidence: 99%
See 3 more Smart Citations